The Lexical and Grammatical Semantic in the Poem Ahinnu Ila Khubzi Ummi by Mahmoud Darwish: The Perspective of Abdul Chaer - Nabila , Alifah Sausan; Yurisa, Penny Respati (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
In producing a poem, it is not uncommon for a writer to produce a poem that contains implied meaning through the use of figurative language or metaphors. This encourages readers to think more deeply in order to understand the meaning conveyed by the author through the figurative language he uses. The objectives of tjis study are : 1) to describe the lexical meaning in the poem Ahinnu Ila Khubzi Ummi based on Abdul Caher’s perspective, 2) to describe the grammatical meaning in the poem Ahinnu Ila Khubzi Ummi based on Abdul Chaer’s perspective. The theory used in this study is the lexical and grammatical semantic theory proposed by Abdul Chaer. This research is descriptive qualitative research with data collection techniques in the form of reading and note-taking, while the data analysis technique uses the Miles and Huberman model, which is divided into three stages, namely data reduction, data presentation, and conclusion drawing. The primary data source for this study is the lines in the poem Ahinnu Ila Khubzi Ummi by Mahmoud Darwish and its translation, while the secondary data used in this study is form several books and journals related to this study. The result of this study found lexical meanings consisting of synonymy, antonymy, homonymy, hyponymy, polysemy, ambiguity, and reduncacy. Meanwhilw, the grammatical meanings found consisted of affixation, reduplication, and composition.